Frequency of Recurrence of Hepatic Encephalopathy in Patients of Chronic Liver Disease Treated With Rifaximin - Kanwal Arif, Nauman Ismat Butt, Farman Ali, Fahmina Ashfaq, Osama Habib, Aniqa Anser Tufail Khan Kakar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of recurrence of hepatic encephalopathy in patients treated with Rifaximin. Study design: Observational cross-sectional study. Setting & duration: Department of Medicine, Services institute of Medical Sciences Lahore for duration of 12 months. Methodology: Hepatic encephalopathy was diagnosed using West-Haven classification in patients of chronic liver disease. Recurrence was considered if a new episode of hepatic encephalopathy occurred within 3 months after initiation of treatment. A total 120 patients of chronic liver disease having had an episode of recent hepatic encephalopathy within the last 3 months, of both genders, above 20 years of age with hepatic encephalopathy were included in the study. The patients were followed for 3 months after initiation of therapy and any episode of recurrence of hepatic encephalopathy was recorded. Results: Mean age was 51.5±12.2 years and 52.3±12.8 years respectively in Rifaximin and Placebo groups. Fourteen (23.3%) patients in Rifaximin group and 17(28.3%) in placebo group were younger than 40 years of age. Thirty-three (55%) patients in Rifaximin group were male versus 29(48.3%) patients in Placebo group. Fifteen (25%) patients in Rifaximin Group developed hepatic encephalopathy by 3 months of follow up as compared to 31(51.7%) patients in Placebo Group Conclusion: Frequency of recurrence of hepatic encephalopathy is significantly lower in Rifaximin treated patients. Keywords: Hepatic Encephalopathy, Recurrence, Rifaximin